Preparation and pharmacokinetic study of mebendazole complex with HP-beta-cyclodextrin - Ding, Charles; Ding, Yili; Xu, Zhe; Wang, Peini; Xu, Shufeng (Frontiers in Veterinary Science, 2025)
Mebendazole, approved by the Food and Drug Administration (FDA) in 1974 to expel intestinal parasite infections, was found to exhibit multiple anti-cancer activities. However, due to its poor water solubility (0.33 ± 0.02 μg/mL), its clinical applications were greatly limited. Scientists at Wenzhou-Kean University have developed a formulation that could increase its water solubility as much as 18,333 times to reach 6.05 mg/mL as the best result to date. Through the complexation with HP-beta-cyclodextrin, 80% of mebendazole in the complex was released in vitro in 5 min, and only 20% of mebendazole was released under the same conditions for the pure drug, in a in vivo pharmacokinetic study conducted on dogs with a dose of 5 mg/kg. The Cmax of mebendazole was increased from 8.96 ± 0.15 μg/mL to 17.34 ± 2.02 μg/mL. Tmax of mebendazole was shortened from 12.00 ± 0.50 h to 10 ± 0.50 h. The half lift time was prolonged from 5.81 ± 0.36 h to 10.01 ± 2.07 h; the AUC0-24 was increased from 151.32 ± 5.92 μg·h/mL to 289.02 ± 15.83 μg·h/mL; and the bioavailability was improved by 91%, indicating that this complex can be pushed to the next step as an anti-tumor agent for its clinic practice.